Analysis of the Sensitivity Level of Investment in the Development of Regional Public Hospitals (RSUD) Bhakti Dharma Husada Surabaya City on the Components of Revenue Costs, Management Costs and Interest Rates - Septi, Intan Anastasia; Patriadi, Andi; Sajiyo Sajiyo (International Journal of Mechanical, Electrical and Civil Engineering, 2025)
Since its first operation in 2010, Bhakti Dharma Husada Regional Public Hospital (RSUD) has experienced an increase in patient demand for health services. Some services now require additional space. Moreover, there is a growing need for executive and VIP services. To address these needs, Bhakti Dharma Husada Regional Public Hospital is planning to enhance its services by constructing a new building. Based on the results of investment analysis obtained Net Present Value (NPV) of Rp. 1,373,606,103,022, Payback Period (PP) for 6.89 years, Internal Rate of Return (IRR) value of 17.39% is greater than the Minimum Attractive Rate of Return (MARR) value of 9.21% (IRR> MARR), Benefit Cost Ration (BCR) of 1.28, then the investment is declared feasible. In addition, based on the results of the sensitivity analysis, the investment feasibility limit is obtained, namely the development of the hospital becomes unfeasible if the service tariff is reduced by 15% or the operating costs are increased by 15% or the interest rate is increased by 13%.